Pengetahuan Keuangan, Gaya Hidup Dan Pendapatan Mempengaruhi Pengelolaan Keuangan Pada Karyawan Ritel Modern Di Kabupaten Sumbawa - Hartini Hartini; Nia Murnia (Universitas Hamzanwadi, 2021)
In this modern and increasingly sophisticated era, various types of markets have emerged, one of which is modern retail. Many modern retailers open up job opportunities for those who have just finished their studies. This study aims to examine whether financial knowledge, lifestyle and income affect the financial management of modern retail employees in Sumbawa Regency. This study uses quantitative methods. The sample in this study amounted to 100 respondents obtained by non-probability sampling method with purposive sampling technique. The data obtained were processed using multiple linear analysis techniques SPSS software. The results of the analysis of this study indicate that (1) the financial knowledge variable has a positive and significant influence on financial management for modern retail employees in Sumbawa Regency. (2) lifestyle variables have a positive and significant influence on financial management of modern retail employees in Sumbawa Regency. (3) income variable has a positive and significant effect on financial management of modern retail employees in Sumbawa Regency